Social support for hearing parents raising deaf children in Kazakhstan: challenges and solutions - Zhansaya Janpeisova; Assel Sarsenova; Karlygash Yessenamanova; Kulmarash Kashkinbayeva (Institute of Advanced Engineering and Science, 2026)
In Kazakhstan, social support for families with hearing-impaired children remains a pressing issue requiring further research and improvement. The aim of this study is to assess the social support provided to families of hearing parents with children who have hearing impairments in Kazakhstan. The study involved 176 families from Kazakhstan, in which the parents are hearing, and the children have hearing loss. This study employed a convergent mixed-methods approach, combining the simultaneous collection and analysis of qualitative (interviews) and quantitative (surveys) data with the subsequent integration of the findings to gain a more comprehensive understanding of the situation. The results showed that 89% of respondents were aware of existing social assistance programs; financial and medical support were considered particularly important, while psychological support was deemed insufficient. Socioeconomic and geographic factors significantly influenced access to services. The data also showed that income level and type of settlement significantly influence families’ access to social services and awareness of support programs, while the age of parents and children has less influence, although the needs of children of different ages vary. The practical significance of the study lies in identifying problems within the social assistance system, such as low information accessibility, long waiting times, inadequate support, and service quality fluctuations. The obtained data can be used to improve social support mechanisms and raise awareness among families with children who have hearing impairments. These findings can be used to improve social support mechanisms and raise awareness of this issue among families with hearing-impaired children.